Manufacturing Process for Improved Ultra‐Thick Cathodes in High‐Energy Lithium‐Ion Batteries. Issue 2 (6th June 2019) - Kremer, Lea Sophie; Hoffmann, Alice; Danner, Timo; Hein, Simon; Prifling, Benedikt; Westhoff, Daniel; Dreer, Christian; Latz, Arnulf; Schmidt, Volker; Wohlfahrt-Mehrens, Margret
Abstract : The effect of the mixing and drying process on the microstructure of ultra‐thick NCM 622 cathodes (50 mg cm −2, 8 mAh cm −2 ) and its implication for battery performance is investigated. It is observed that the shear force during the mixing process significantly influences the resulting microstructure with regard to binder migration during the drying process. Based on the information extracted from scanning electron microscopy–energy dispersive X‐ray spectroscopy (SEM–EDX) cross sections, the carbon binder domain (CBD) is distributed in the pore space of virtual electrodes generated by a stochastic 3D microstructure model. Simulations predict a CBD configuration that leads to optimal performance of the electrode. Furthermore, it is shown that a low drying rate has a beneficial influence toward the rate capability of the ultra‐thick cathodes. The specific energy of an ultra‐thick cathode is 18% higher compared with a cathode prepared according to the state of the art. With an improved process in a pilot scale, the advantage can be kept up to current densities of at least 3 mA cm − ². Abstract : Ultra‐thick electrodes promise a higher energy density and a better ratio of active to inactive cell components than state‐of‐the‐art electrodes. By application of an improved manufacturing process, ultra‐thick cathodes (50 mg cm −2 ) with an enhanced rate capability were yielded, that provide an 18% higher specific energy at a current density of 1 mA cm −2 compared with a state‐of‐the‐art cathode (20 mg cm −2 ).